2016
DOI: 10.1523/eneuro.0143-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Normal Performance of Fmr1 Mice on a Touchscreen Delayed Nonmatching to Position Working Memory Task

Abstract: Fragile X syndrome is a neurodevelopmental disorder characterized by mild-to-severe cognitive deficits. The complete absence of Fmr1 and its protein product in the mouse model of fragile X (Fmr1 KO) provides construct validity. A major conundrum in the field is the remarkably normal performance of Fmr1 mice on cognitive tests in most reports. One explanation may be insufficiently challenging cognitive testing procedures. Here we developed a delayed nonmatching to position touchscreen task to test the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…Touch-screen automated paradigms have become increasingly utilized to screen rodent models of numerous neuropsychiatric disorders (Marquardt et al, 2014, Yang et al, 2015, Copping et al, 2016, Leach et al, 2016) as these paradigms closely model tools used in the clinical assessment and may increase translational potential of preclinical studies (Mar et al, 2013, Talpos and Steckler, 2013, Hvoslef-Eide et al, 2016). While previous studies have demonstrated that lesion and/or inactivation of the region is sufficient to disrupt visual touch-screen reversal, it has not yet been demonstrated that the rodent OFC mediates reversal of complex visual stimuli in an analogous manner to those seen in primates using visual stimuli (Clarke et al, 2008), or to more species-specific stimuli such as spatial, olfactory or tactile stimuli in rodents (Hamilton and Brigman, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Touch-screen automated paradigms have become increasingly utilized to screen rodent models of numerous neuropsychiatric disorders (Marquardt et al, 2014, Yang et al, 2015, Copping et al, 2016, Leach et al, 2016) as these paradigms closely model tools used in the clinical assessment and may increase translational potential of preclinical studies (Mar et al, 2013, Talpos and Steckler, 2013, Hvoslef-Eide et al, 2016). While previous studies have demonstrated that lesion and/or inactivation of the region is sufficient to disrupt visual touch-screen reversal, it has not yet been demonstrated that the rodent OFC mediates reversal of complex visual stimuli in an analogous manner to those seen in primates using visual stimuli (Clarke et al, 2008), or to more species-specific stimuli such as spatial, olfactory or tactile stimuli in rodents (Hamilton and Brigman, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Once mice acquire TUNL, further manipulations can be carried out by varying delay, spatial separation level and ITI (McAllister et al 2013 ). At least one other group has reported success training mice on this task in a similar, simplified manner (Leach and Crawley 2014 ). Note that although we had success with one method for the mouse, it may be that by varying other task parameters, alternative or additional improvements could be made.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are still two conserved parallel pathways between the cortex and the hippocampus in mice and men, which transfer object and context related information (reviewed in Ranganath and Ritchey, 2012 ), the finding of Bergmann and colleagues is of quiet some significance since cortical-hippocampal pathways are required for important brain functions including spatial working memory (studies in rodents and humans; reviewed in Sigurdsson and Duvarci, 2016 ), long-term memory (studies in rodents, primates and humans; reviewed in Sigurdsson and Duvarci, 2016 ), motivation and emotion (studies in rodents; reviewed in Sigurdsson and Duvarci, 2016 ), and social recognition (studies in rodents and humans; reviewed in Bicks et al, 2015 ). Indeed, weaknesses in working memory performance, in particular when requiring abstract item reasoning, are characteristic to FXS patients (Munir et al, 2000 ; Cornish et al, 2001 ; Kwon et al, 2001 ; Ornstein et al, 2008 ; Baker et al, 2011 ; Wang et al, 2013 ), but not to model mice (Leach et al, 2016 ). While Fmr1 −/y mice perform as well as their wildtype littermates even when their working memory is significantly challenged (Leach et al, 2016 ), individuals with FXS are unable to modulate activation of the prefrontal and parietal cortex in response to an increasing working memory load (Kwon et al, 2001 ), implying a lack of circuit control.…”
Section: From Mice To Menmentioning
confidence: 99%